A Comparison of the Accuracy of Liquid Cytology Versus Conventional Screening: A Meta-Analysis of Split-Sample Studies. (7th February 2013) - Epstein, David; Labry Lima, de Antonio Olry; Mochón, Leticia García; Balbino, Jaime Espín; Esquivias, Javier
Summary: The aim of the paper is to compare the accuracy and effectiveness of liquid-based versus conventional cytology when used as part of a process of population screening to reduce the incidence of invasive cervical cancer. Data from split-sample studies were analysed by using a hierarchical Bayesian multiparameter evidence synthesis model. Predictions of sensitivity and specificity were derived without having a procedure to detect the lesions. Results suggest that the specificity of both tests is high, such that less than 1% of normal samples are expected to be misdiagnosed. However, the sensitivity may be lower, with around 81% of lesions expected to be correctly diagnosed in smear tests and 88% in liquid-based cytology.